Richard Alba and University at Albany President... - Schmidt, Mark (Digital Media Department Records, 2002)
Richard Alba and University at Albany President Karen Hitchcock smiles at an award ceremony for the 2002 Distinguished Professors in the President's Reading Room of the Science Library at the University at Albany. [20002308]